Una propuesta de reforma de la Facultad de Ingeniería - Betancourt Uscategui, Álvaro (Ingeniería, 1999)
Under the current conditions and in short term projection it is necessary to trace so much political as an action plan for the undergraduate, graduate formation, research and extensión activities and to project a modern conception of the Faculty of Engineering.